Use of DBS sample collection to determine circulating drug concentrations in clinical trials: practicalities and considerations. (August 2010) - Spooner, Neil; Ramakrishnan, Y; Barfield, M; Dewit, O; Miller, S
Background: A clinical investigation was performed into the practicalities of the collection of blood samples for the determination of drug exposures on filter paper, known as dried blood spot (DBS) sampling using a two-period, single-dose, open-label trial conducted in 11 healthy volunteers who received a single oral dose of paracetamol. Questionnaires relating to the blood sampling and spotting process and tolerability were completed by staff and volunteers. Paracetamol concentrations in DBS samples obtained by venous cannula (DBS-Can) were compared against those from fingerprick (DBS-FP) and fresh whole blood obtained from a cannula (WB-Can).Results: The questionnaires demonstrated that FP and blood spotting was easy to perform and well tolerated and compared favorably with cannula sampling. Paracetamol concentrations in DBS-Can were greater than those in WB-Can (positive bias) except below 8000 ng/ml when both were interchangeable. When comparing DBS-FP to DBS-Can, both the bias and variability differed significantly across the five sampling time points.Conclusion: The study has shown that the DBS technique is practical in the context of a clinical trial. Interchangeability of drug concentrations between blood sampling site and mode of blood collection has to be checked and taken into account when designing pharmacokinetic studies for other compounds.